Quality of public spaces: The main commercial offer driving the attractiveness of public spaces in El khroub - Chaabna, Abdelkrim; Alkama, Djamel (Journal of Architecture and environment of child, 2021)
The evolution of the city, its rhythms, the changes in its spaces and their uses raise the question of the issues and interests of the requalification of public spaces from the point of view of their symbolic, aesthetic and functional value. This article examines how the commercial offer can participate in the creation of attractive and convivial public spaces in the centers as in the peripheral areas of the city of El khroub. We will try to show that commercial expansion, structure and modulate the attractiveness of public spaces, influence the spatial characteristics of inhabitants and strengthen the social links of neighbourhoods. Our method is almost exclusively dependent on the field surveys that we carried out during the first quarter of 2019. To this end, this work essentially explores the impact of the market dimension on the urban quality of public space of El khroub.